Primality test and primes enumeration using odd numbers indexation - Wolf, Marc; François, WOLF (Transactions on Engineering and Computing Sciences, 2020)
Odd numbers can be indexed by the map k(n)=(n-3)⁄2,n∈2N+3. We first propose a basic primality test using this index function that was first introduced in [8]. Input size of operations is reduced which improves computational time by a constant. We then apply similar techniques to Atkin’s prime-numbers sieve which uses modulus operations and finally to Pritchard’s wheel sieve, in both case yielding similar results.